2021
DOI: 10.1088/2631-8695/abd4f1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and prediction of the tensile strength of aluminum alloy composite using statistical and artificial neural network technique

Abstract: In this research work, aluminum alloy (Al-20Fe-5Cr) matrix-based aluminum oxide (Al 2 O 3 ) reinforced composites were developed through the powder metallurgy (P/M) process. Effect of compaction pressure (200, 250 & 300 MPa) and wt.% of Al 2 O 3 (0, 10, 20 & 30 wt.) on tensile strength and percentage elongation has been analyzed through statistical and artificial neural network techniques (ANN). The mixture of Al-alloy powder particles and Al 2 O 3 particles were synthesized in a centrifugal ball mill for 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…The histogram using the standardised residual in this study suggests that there is reduced skewness and no outliers. The residuals have been seen from the smallest to the greatest range, confirming that the produced results are accurate and precise [3,30,31].…”
Section: Anova Implementation For Wear Losssupporting
confidence: 65%
“…The histogram using the standardised residual in this study suggests that there is reduced skewness and no outliers. The residuals have been seen from the smallest to the greatest range, confirming that the produced results are accurate and precise [3,30,31].…”
Section: Anova Implementation For Wear Losssupporting
confidence: 65%
“…Modeling and optimizing the processing parameters and chip morphology can significantly contribute to improving the chip-based recycled strength. Recently, there has been a growing interest in utilizing advanced techniques, such as Response Surface Methodology (RSM) and Machine Learning (ML), to model and optimize the performance of manufacturing processes [23][24][25][26][27]. The aluminum waste recycling parameters have been modeled using RSM [10,11,28,29] and ANN [26,[30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been a growing interest in utilizing advanced techniques, such as Response Surface Methodology (RSM) and Machine Learning (ML), to model and optimize the performance of manufacturing processes [23][24][25][26][27]. The aluminum waste recycling parameters have been modeled using RSM [10,11,28,29] and ANN [26,[30][31][32][33][34]. Moghri et al [35] reported that RSM and genetic algorithm effectively identified the optimum process variables for maximum tensile modulus and tensile strength of PA-6/clay nanocomposite.…”
Section: Introductionmentioning
confidence: 99%
“…The results determined that the trained model effectively predicted the mass loss with the least amount of error. Mohsin et al [15] used ANN to predict the tensile properties of Al composite. Pressure and wt% of reinforcement were used as input parameters, UTS and % elongation were used as output parameters.…”
Section: Introductionmentioning
confidence: 99%